STUDI PENGAJARAN BAHASA ARAB DALAM MENINGKATKAN PENGUASAAN MUFRODAT SISWA KELAS XI SMA AL-FALAH BANDUNG - Handri Setiadi (LUGATUNA: Jurnal Prodi PBA, 2023)
This research study contains problems related to the difficulties of teaching Arabic in increasing mastery of mufrodat. To be able to develop four proficiency in Arabic, students need to master mufrodat first through teaching Arabic. This study aims to describe teaching Arabic in improving students' mufrodat mastery. The things studied include planning, implementation, methods, and evaluation of teaching in improving students' mufrodat mastery. The method used in this research is a qualitative method with a descriptive approach design. The research samples were Arabic teachers and students of class XI SMA Al-Falah Bandung. Data regarding teaching Arabic in improving the mastery of mufrodat is obtained from observations, documentation studies, and interviews. Data analysis was carried out by qualitative analysis with a descriptive approach. This research gave rise to teaching studies including; teaching planning, teaching implementation, teaching methods, to teaching evaluation. After the data is processed and discussed, the results of the analysis show that teaching Arabic in class XI SMA Al-Falah Bandung is mostly in accordance with the underlying theory. However, there are also some that are not appropriate, causing various teaching difficulties in improving students' mastery of mufrodat. Such as difficulties in planning, difficulties in implementation, difficulties in methods, and difficulties in evaluating Arabic teaching. From these difficulties, suggestions for improvement were found so that teaching Arabic could further improve students' mufrodat mastery